2012
DOI: 10.1111/tpj.12053
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the cinnamyl alcohol dehydrogenase 1 gene (BdCAD1) leads to altered lignification and improved saccharification in Brachypodium distachyon

Abstract: SUMMARYBrachypodium distachyon (Brachypodium) has been proposed as a model for grasses, but there is limited knowledge regarding its lignins and no data on lignin-related mutants. The cinnamyl alcohol dehydrogenase (CAD) genes involved in lignification are promising targets to improve the cellulose-to-ethanol conversion process. Down-regulation of CAD often induces a reddish coloration of lignified tissues. Based on this observation, we screened a chemically induced population of Brachypodium mutants (Bd21-3 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 67 publications
2
96
0
1
Order By: Relevance
“…Therefore, at least part of the lower Glc release is due to the reduced cellulose content in the leaves of C2-Idf plants. It has been established that saccharification efficiency is negatively correlated with lignin amount in both monocot and dicot species (Chen and Dixon, 2007;Sattler et al, 2010;Xu et al, 2011;Bouvier d'Yvoire et al, 2013;Jung et al, 2013;Van Acker et al, 2013;Vanholme et al, 2013a) and that a lower degree of polymerization of lignin eases its extraction from the biomass (Eudes et al, 2012;Vanholme et al, 2012;Shen et al, 2013). The alkaline pretreatment hydrolyzes ester bonds, thereby releasing (di)ferulates that acylate the hemicellulose (and of which a part is also coupled to lignin) and p-coumarates that additionally acylate the lignin backbone (Ralph, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at least part of the lower Glc release is due to the reduced cellulose content in the leaves of C2-Idf plants. It has been established that saccharification efficiency is negatively correlated with lignin amount in both monocot and dicot species (Chen and Dixon, 2007;Sattler et al, 2010;Xu et al, 2011;Bouvier d'Yvoire et al, 2013;Jung et al, 2013;Van Acker et al, 2013;Vanholme et al, 2013a) and that a lower degree of polymerization of lignin eases its extraction from the biomass (Eudes et al, 2012;Vanholme et al, 2012;Shen et al, 2013). The alkaline pretreatment hydrolyzes ester bonds, thereby releasing (di)ferulates that acylate the hemicellulose (and of which a part is also coupled to lignin) and p-coumarates that additionally acylate the lignin backbone (Ralph, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, all studied species had the common feature that down-regulating CAD caused the incorporation of hydroxycinnamaldehydes into the lignin polymer. The presence of hydroxycinnamaldehydes during lignin polymerization typically results in a reddish-brown coloration of the xylem (Halpin et al, 1994;Baucher et al, 1996Baucher et al, , 1999Ralph et al, 1997;Lapierre et al, 1999Lapierre et al, , 2004Chabannes et al, 2001;Pilate et al, 2002;Sibout et al, 2005;Zhang et al, 2006;Jackson et al, 2008;Vermerris et al, 2010;Bouvier d'Yvoire et al, 2013), a coloration that results not from the lignin itself but from side reactions of the hydroxycinnamaldehydes (Kim et al, 2002;Fournand et al, 2003;Ralph et al, 2008). In poplar, CAD has been down-regulated previously by sense and antisense constructs.…”
mentioning
confidence: 99%
“…(pine;MacKay et al, 1997;Ralph et al, 1997;Wu et al, 1999), maize (Halpin et al, 1998;Vermerris et al, 2010;Fornalé et al, 2012), Panicum virgatum (switchgrass; Fu et al, 2011;Saathoff et al, 2011), Eucalyptus camaldulensis (Valério et al, 2003), Oryza sativa (rice; Zhang et al, 2006;Li et al, 2009), alfalfa (Baucher et al, 1999;Jackson et al, 2008), and brachypodium (Bouvier d'Yvoire et al, 2013). Most of these studies focused on the consequences of down-regulating CAD expression on lignin content and composition, and several studies also investigated the biomass properties of these CAD-deficient plants for industrial applications like pulping or biofuel production (Baucher et al, 1996;Lapierre et al, 1999;Pilate et al, 2002;Sibout et al, 2005;Jackson et al, 2008;Fu et al, 2011;Saathoff et al, 2011;Fornalé et al, 2012;Bouvier d'Yvoire et al, 2013;Anderson et al, 2015). Depending on the studied species, the lignin content and composition (S/G ratio) either remained equal or were reduced, independently of each other, compared with the corresponding control line.…”
mentioning
confidence: 99%
“…CmCAD4 was considered a pseudogene, being not expressed or expressed at low levels in lignified tissues (Jin et al 2014), as observed in TgCAD1. Additionally, Liriodendron tulipifera LtuCAD1 , Brachypodium distachyon BdCAD1 (Trabucco et al 2013;Bouvier d'Yvoire et al 2013), Ginkgo biloba GbCAD1 (Cheng et al 2013) and Lolium perenne LpCAD1-3 (Lynch et al 2002) were expressed in lignifying tissues, as observed in TgCAD4. In Populus, the PtCAD10 gene, which is close to TgCAD3 and TgCAD4 phylogenetically (Figure 3), was 100-times more expressed in xylem compared to other CAD genes.…”
Section: Differential Expression Of Tgcad Gene Familymentioning
confidence: 99%
“…Class III is a monophyletic clade responsible for plant development but not related with lignin biosynthesis (Guo et al 2010). Recently, CAD gene has been explored through downregulation by reverse genetics in several species, including dicot and monocot plants (Anterola and Lewis 2002;Valério et al 2003;Vanholme et al 2010;Bouvier d'Yvoire et al 2013;Preisner et al 2014). CAD antisense gene expression in poplar (Pilate et al 2002;Baucher et al 2003) and eucalyptus (Valério et al 2003) trees allowed a suitable woody tissue usage for agro-industrial purposes without compromising tree growth.…”
Section: Introductionmentioning
confidence: 99%